Influence of Photopolymerization Characteristics on Thermo‐Mechanical Properties of Nanocomposites Utilizing Polymerizable Organoclays in Thiol‐Acrylate Systems. Issue 1 (23rd August 2013) - Kim, Soon Ki; Baguenard, Céline; Guymon, C. Allan; Bowman, Christopher N.; Horkay, Ferenc
Summary To produce clay nanocomposites, photopolymerizable organoclays can react with monomers and incorporate into polymer matrices during the UV curing process. This research investigates the effects of polymerizable organoclays on the reaction behavior as well as the ultimate composite properties based on in‐situ thiol‐ene photopolymerization. To this end, different types of polymerizable organoclays, prepared by changing the functional group structure, were examined in various thiol‐acrylate systems. Small angle X‐ray diffraction was used to examine the degree of clay exfoliation. Photopolymerization behavior was characterized using real time infrared spectroscopy. Dynamic mechanical analysis was used for analyzing both mechanical and thermal properties. With sufficient clay exfoliation, the incorporation of thiol groups on the clay surfaces significantly increases the photopolymerization rate and final thiol conversion, whereas acrylate group conversion does not change significantly. While increasing monomer functionality does decrease final thiol conversion, the increase of thiol functionality of organoclays enhances thiol‐ene step growth reaction. Dark curing results suggest that the structure of propagating radicals on the clay surface varies by the type of polymerizable organoclays, changing the reaction behavior of the system. In accordance with the reaction behavior, the incorporation of acrylated organoclays significantly increases the storage modulus by inducing dominant acrylate homopolymerization. Addition of thiolated organoclays, on the other hand, makes more flexible polymer chains due to increased thio‐ether linkages.